2012
DOI: 10.1111/tri.12018
|View full text |Cite
|
Sign up to set email alerts
|

Do drug transporter (ABCB1) SNPs and P-glycoprotein function influence cyclosporine and macrolides exposure in renal transplant patients? Results of the pharmacogenomic substudy within the symphony study

Abstract: SummaryThe function of the efflux pump P-glycoprotein (Pgp) and ABCB1 single nucleotide polymorphisms (SNPs) should be considered as important tools to deepen knowledge of drug nephrotoxicity and disposition mechanisms. The aim of this study is to investigate the association of C3435T, G2677T, C1236T, and T129C ABCB1 SNPs with Pgp activity and exposure to different immunosuppressive drugs in renal transplant patients. Patients included in the Symphony Pharmacogenomic substudy were genotyped for ABCB1 SNPs. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Specifically, women and patients with at least one CYP3A5⁄1 or CYP3A4⁄18B allele would require significantly higher doses of cyclosporine to reach target drug levels than patients with the CYP3A5⁄3 or CYP3A4⁄1 alleles. What our study neglected to address is how P-glycoprotein (P-gp) activity may affect the bioavailability of cyclosporine (Llaudó et al, 2013). Specifically, patients with a CT or CC nucleotide exchange in exon 26 (C3435T) with high P-gp activity may result in decreased bioavailability of cyclosporine.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, women and patients with at least one CYP3A5⁄1 or CYP3A4⁄18B allele would require significantly higher doses of cyclosporine to reach target drug levels than patients with the CYP3A5⁄3 or CYP3A4⁄1 alleles. What our study neglected to address is how P-glycoprotein (P-gp) activity may affect the bioavailability of cyclosporine (Llaudó et al, 2013). Specifically, patients with a CT or CC nucleotide exchange in exon 26 (C3435T) with high P-gp activity may result in decreased bioavailability of cyclosporine.…”
Section: Discussionmentioning
confidence: 98%
“…ABCB1, also known as MDR1 (multidrug resistant gene), is a part of the ABC transporter superfamily. It encodes a P‐glycoprotein (Pgp), which was first described in multi‐drug resistant cells . It is involved in absorption, disposition, and metabolism of drugs .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in the patients with a CT or CC nucleotide exchange (high pumpers) in exon 26 (C3435T) with high Pgp activity on the apical surface of intestinal enterocytes, more CsA is removed from the cells, which results in decreased bioavailability. [49] In this context, patients (high pumpers) treated with low doses of CsA would show lower drug exposure and this could affect MPA AUC exposure. [17,49] …”
Section: Discussionmentioning
confidence: 99%
“…[49] In this context, patients (high pumpers) treated with low doses of CsA would show lower drug exposure and this could affect MPA AUC exposure. [17,49] …”
Section: Discussionmentioning
confidence: 99%